Big Data Challenges And Opportunities In The Development Of Digital Technology - Dara Sawitri (Jurnal Info Sains : Informatika dan Sains, 2024)
At this time big data, with large data volumes that continue to grow and become complex, is a challenge and opportunity for governments and organizations. This is said to be a challenge considering that the increase in data volume will produce a lot and variety of information, thus requiring efficient ways of storing and managing data. Big data is said to be an opportunity considering that the magnitude of the study results and proper information management will open up new opportunities to recognize the potential for improving services in various government and organizational sectors. Big data can open up opportunities to increase knowledge about various aspects of people's lives so that it can encourage the creation of new trends and innovations in various fields, improve and optimize operations, and determine future conditions so that governments and organizations can produce appropriate basic products. In the future, big data will change the way governments and organizations run their operations, creating challenges and opportunities for decision-makers. Even so, in the future big data can be utilized more optimally for the benefit of the wider community. In the future, big data has great potential to be used in many sectors to improve people's welfare. By using the right methods, big data can be very valuable in improving the welfare and quality of life of the wider community. Therefore, to be able to implement big data to improve the welfare and quality of life of the wider community, it is necessary to understand the challenges and opportunities of big data in the development of digital technology.